2016
DOI: 10.1016/j.midw.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

How optimal caseload midwifery can modify predictors for preterm birth in young women: Integrated findings from a mixed methods study

Abstract: the institutional infrastructure and managerial support for caseload midwifery should value and prioritise the philosophical commitments and personal attributes required to optimise the model. Furthermore the location of visits, between appointment access to primary midwife, and back-up system should be organised to optimise the midwife-woman relationship in order to promote the young woman's engagement with maternity care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 83 publications
1
37
0
Order By: Relevance
“…Trusting relationships are the foundation on which CMC is built and become the cement that holds it together over time. Relationships matter, not only because women want them, but because it is the woman-midwife relationship that triggers change in women's behaviour [69] and midwives' practice resulting in better outcomes and care giving experience. The importance of womanmidwife relationships are already recognised, as are the supportive, sustaining and enabling relationships between midwives within CMC teams [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trusting relationships are the foundation on which CMC is built and become the cement that holds it together over time. Relationships matter, not only because women want them, but because it is the woman-midwife relationship that triggers change in women's behaviour [69] and midwives' practice resulting in better outcomes and care giving experience. The importance of womanmidwife relationships are already recognised, as are the supportive, sustaining and enabling relationships between midwives within CMC teams [48].…”
Section: Discussionmentioning
confidence: 99%
“…Allen et al, [69] identified 'Synergistic Health Engagement' as the mechanism by which optimal caseload midwifery (comprising philosophical commitment, institutional infrastructure and support, and personal attributes) modified the risks of preterm birth through women both attending and buying in (emotional investment and commitment) to services. In our study this mechanism might also explain the impact of caseloading on the midwife who through her relationship with women 'bought in' to CMC to ensure women had good experiences and outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of women's satisfaction with childbirth reported that feeling supported by caregivers, having a high quality caregiver-patient relationship, and feeling involved in decision-making were factors so important to women that they overrode differences in age, ethnicity and socioeconomic status (Hodnett, 2002). The midwife's personal characteristics and philosophical commitments affect the nature and quality of the partnership in caseload midwifery models (Allen et al, 2016). In the largest trial of caseload midwifery (n=2,314), participants allocated to the intervention: "felt more in control during labour, were more proud of themselves, less anxious, and more likely to have a positive experience of pain" compared to participants in standard care (McLachlan et al, 2016, p.465).…”
Section: Personal Attributesmentioning
confidence: 99%
“…Trusting relationships are the foundation on which CMC is built and become the cement that holds it together over time. Relationships matter, not only because women want them, but because it is the woman-midwife relationship that triggers change in women's behaviour(69) and midwives' practice resulting in better outcomes and care giving experience. The importance of woman-midwife relationships are already recognised, as are the supportive, sustaining and enabling relationships between midwives within CMC teams(48).…”
mentioning
confidence: 99%